2019
DOI: 10.3389/fphys.2019.00224
|View full text |Cite
|
Sign up to set email alerts
|

Axon Guidance-Related Factor FLRT3 Regulates VEGF-Signaling and Endothelial Cell Function

Abstract: Vascular endothelial growth factors (VEGFs) are key mediators of endothelial cell (EC) function in angiogenesis. Emerging knowledge also supports the involvement of axon guidance-related factors in the regulation of angiogenesis and vascular patterning. In the current study, we demonstrate that fibronectin and leucine-rich transmembrane protein-3 (FLRT3), an axon guidance-related factor connected to the regulation of neuronal cell outgrowth and morphogenesis but not to VEGF-signaling, was upregulated in ECs af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Much was learned about angiogenesis with the discovery of vascular endothelial growth factor (VEGF). VEGF appears to be intimately involved with wound repair [41] and wound repair requires angiogenesis [42,43]. Others have shown that healthy ECs produce VEGF, which helps control body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Much was learned about angiogenesis with the discovery of vascular endothelial growth factor (VEGF). VEGF appears to be intimately involved with wound repair [41] and wound repair requires angiogenesis [42,43]. Others have shown that healthy ECs produce VEGF, which helps control body weight.…”
Section: Discussionmentioning
confidence: 99%
“…The fibronectin leucine rich transmembrane protein (FLRT) family may function in cell adhesion and/or receptor signaling [51]. Jauhiainen et al described the role of FLRT3 in the regulation of angiogenesis and vascular patterning via modulation the VEGF-signaling [52]. Moreover, gene-targeting experiments in mice demonstrate demonstrated that Flrt2 is required in the epicardium to promote heart morphogenesis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that mice lacking FLRT2 in vascular endothelial cells exhibit embryonic lethality at mid-gestation with systemic congestion and hypoxia (Tai-Nagara et al, 2017). Notably, FLRT3 is a newly identified member of a family of axon guidance-related factors that participate in VEGFsignaling and regulation of endothelial cell functions (Jauhiainen et al, 2019). We observed that FLRT2 is expressed in the vascular endothelial cells of the hippocampus in adult mice, indicating that FLRT2 may play a key role in maintenance of vascular morphology and function at various stages of development.…”
Section: Discussionmentioning
confidence: 99%